Educação interseccional: práxis transformadora de educadores/as sociais no enfrentamento ao epistemicídio - Martins, Maíra Caroline (2022)
Racist and sexist relationships historically continue structuring everyday experiences, and sometimes, composing the subjectivity of education professionals and practices in formal and non-formal educational spaces. When the problem is faced, it is still observed the occurrence of approaches that are sometimes conservative and relativizing. The main objective of this dissertation is to analyze practices that are configured as intersectional transformative praxis in non-formal education curricula, based on the relationship between popular education, curriculum, decolonial feminisms and critical studies of whiteness, pointing out possible ways to intensify the confrontation of the problem. of racist/macho epistemicide in educational spaces. The methodology used is of a qualitative approach, having as procedures bibliographic research, document analysis and field research, considering the importance of reflecting on praxis in a dialogic way. The authors who base the methodological procedures are Marli EDA Andre and Menga Ludke (1986), Antônio Carlos Gil (2019) and Tereza Maria Spyer Dulci and Mariana Rocha Malheiros (2021), in addition to several authors who are listed as reference in the literature. theoretical basis of the research. Official documents from Sesc São Paulo, the locus of the field research that integrates the dissertation, were analyzed, as well as laws and guidelines for formal education that have applicability in non-formal contexts. The field research was carried out through interviews based on a semi-structured script in a conversation circle format, having as interlocutors the social educators of the Tecnologias e Artes, Curumim and Juventudes programs at Sesc São Paulo. Among the results of the analyses, the outline of a path towards a transforming praxis stands out, a path that has as its foundations the awareness of the practice itself, the awareness of the institutional values of the space where the educational action is developed, which must have as presuppositions the experience of democratic values in the reception and appreciation of social educators committed to intersectional education and transformative praxis, in addition to the social educator's awareness of his/her own praxis, and the exercise of this praxis same a personal and professional value